Trajectory-Based Optimal Area Forwarding for Infrastructure-to-Vehicle Data Delivery with Partial Deployment of Stationary Nodes. (17th April 2013) - Chen, Liang-Yin; Fu, Song-Tao; Zhang, Jing-Yu; Zou, Xun; Liu, Yan; Yin, Feng
This paper proposes a trajectory-based optimal area forwarding (TOAF) algorithm tailored for multihop data delivery from infrastructure nodes (e.g., Internet access points) to moving vehicles (infrastructure-to-vehicle) in vehicular ad hoc networks (VANETs) with partial deployment of stationary nodes. It focuses on reducing the delivery-delay jitter and improving the low reliability of infrastructure-to-vehicle communication. To adapt with the real world, TOAF supposes that stationary nodes are partially installed at intersections in VANETs, and nodes' trajectories can be calculated and predicted, such as using cloud services and GPS, to find the optimal area where the destination vehicle may receive a packet timely. AP selects the optimal area from the trajectory of the destination vehicle and determines the delivery sequence, which includes stationary and mobile nodes from the AP to the optimal area. During delivery, if a new node finds that the delay to the next stationary node is less than that of the current carrier, it can be added to the sequence, reducing the delivery delay. The addition of a new node continues until the packet reaches the optimal area and infrastructure-to-vehicle communication is achieved. The simulation results confirm that TOAF can improve the performance of delivery-delay jitters and reliability of infrastructure-to-vehicle communication with partial deployment of stationary nodes.